Dryland Agriculture: Coping with Climate Change - Venkateswarlu, B (Annals of Arid Zone, 2016)
Climate change impacts on agriculture are being witnessed all over the world. There are reports of negative impacts of increasing temperature and water stress on crop yields in India. The projected climate change is likely to further aggravate yield variations of many crops, particularly in rainfed situations. For successful adaptation to climate change we need to document the indigenous practices adopted by farmers for coping with climate variability, adaptation and mitigation potential of the existing best bet practices and a long term research plan to evolve new tools and techniques that help in adaptation. Selection of crops and varieties that fit into changed rainfall and temperature scenario, development of varieties for heat, drought and submergence tolerance and evolving varieties responsive to high CO2 concentrations with high fertilizer and radiation use efficiency should receive high priority for adaptation research. Germplasm of wild relatives and local land races could prove valuable source of climate ready traits. Agroforestry systems like agri-silviculture, silvi-pasture and agri-horticulture offer both adaptation and mitigation opportunities. A large number of technological options are available for soil, water and nutrient management that may contribute to both adaptation and mitigation. Some important examples include in- and ex-situ moisture conservation, rainwater harvesting and recycling, efficient use of irrigation water, use of poor quality water, conservation agriculture, integrated and site-specific nutrient management and energy efficiency in agriculture. Watershed management is an accepted approach for development of rainfed agriculture. Integration of national development policies into a sustainable development framework that complement adaptation will be required to accompany the available technological options